Interactive effect of dietary metabolizable energy levels with amino acid density in male broiler chickens: Carcass yield, nutrient intake, digestibility and excretion - Mehdi Toghyani; Shemil MacElline; Peter H. Selle; Sonia Y. Liu (Poultry Science, 2025)
This study aimed to assess the interactive effects of ME and digestible amino acid (AA) densities on carcass yield, breast meat quality, nutrient digestibility, and excretion in male broiler chickens. Twelve experimental diets arranged as a 4 × 3 factorial array with 4 levels of ME (standard, -50, -100, -150 kcal) and 3 digestible AA (standard, +3.0 and +6.0%) were offered to 2400 day-old male Ross 308 broiler chickens. Diets were replicated 8 times with 25 birds per replicate, and fed for starter (0-10 d), grower (11-24 d), finisher (25-35 d), and withdrawal (36-42 d) phases, with consistent reduction of ME and increase in AA density for each phase. On day 24, three birds per replicate were euthanized to collect digesta for nutrient digestibility and excreta samples were collected on day 40 for nutrient excretion analysis. On day 42, four birds per replicate were euthanized for carcass yield and quality evaluation. The birds' feed intake, along with calculated ME and AA levels, were used to determine nutrient intake. No interactions were observed between ME and AA densities on carcass characteristics, nutrient digestibility, and excretion (P > 0.05). Reducing ME density linearly increased breast meat yield and decreased abdominal fat, regardless of AA density (P < 0.01). Increasing AA density enhanced breast meat yield but increased white striping and woody breast scores in a linear manner (P < 0.01). Dietary treatments didn't affect ileal digestibility of crude protein and gross energy, except for improved starch digestibility with 6.0% AA density (P < 0.01). Crude fat digestibility decreased linearly with decreased ME density, while reducing ME density linearly decreased fat, calcium, copper, and manganese excretion (P < 0.01). Increasing AA density linearly increased nitrogen excretion, but reduced calcium and iron excretion (P < 0.05). Over the entire production period lower ME and higher AA density increased digestible lysine intake (mg/bird/day; P < 0.01). In summary, these results suggest that dietary ME and AA density, independently, affect carcass yield, breast meat quality, nutrient digestibility, and excretion.